Preparation method and application of ultrahigh-specific-capacity fibrous self-supporting hard carbon negative electrode
Through pre-oxidation and high-temperature carbonization processes, fibrous self-supported hard carbon anode material is prepared, which solves the problems of complex processes and high cost in the prior art, and realizes reversible deposition and peeling of sodium metals at low operating voltages, improving the performance and efficiency of sodium ion batteries.
Patent Information
- Application Number
- CN202510054712.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-03-07
AI Technical Summary
The preparation process of existing hard carbon negative electrode materials is complex and costly, and the problem of deposition of sodium metal at low operating voltage has not been effectively solved, affecting the development of sodium ion batteries.
The precursor material is oxidized and modified by preoxidation strategy, and graphite plates are used to induce redox of oxygen-containing functional groups during high-temperature carbonization to generate small molecule gas to regulate the carbon layer inside the material, and a fibrous self-supported hard carbon anode material is prepared.
The preparation of fibrous self-supported hard carbon anode material with high first-effect and ultra-high specific capacity is achieved, which simplifies the process, reduces costs, and realizes reversible deposition and peeling of sodium metals at low operating voltages, improving the performance of sodium ion batteries.
Smart Images

Figure CN119569034A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of new energy storage materials, and specifically relates to a preparation method and application of a fibrous self-supporting hard carbon negative electrode with ultra-high specific capacity. Background Art
[0002] The development of negative electrode materials is one of the keys to the development and application of sodium-ion batteries. Hard carbon negative electrode has significant advantages such as high specific capacity, long cycle life and good conductivity. It can effectively improve the battery's energy density, charge and discharge efficiency and cycle performance, etc. It is particularly important for the development of electric vehicles, energy storage systems and other fields.
[0003] At present, the preparation process of hard carbon negative electrode materials is closely related to the precursor materials (biomass, asphalt-based, resin-based, etc.), which usually includes the pretreatment of the precursor (crushing, pickling, modification, etc.), high-temperature carbonization and post-treatment (water washing, modification, etc.); by modifying the precursor materials, the first-cycle coulomb efficiency and specific capacity of the hard carbon negative electrode can be effectively improved. However, the complicated modification process will increase the cost of the hard carbon negative electrode, which is not conducive to the development of sodium ion batteries. In order to realize the industrialization of low-cost and high-performance sodium ion batteries, it is necessary to develop a high-performance hard carbon negative electrode material with simple process and excellent performance.
[0004] CN116873902A discloses a hard carbon material, a preparation method thereof and a sodium ion battery based on the hard carbon material, comprising the following steps: S1: soaking paper in dilute sulfuric acid for pretreatment, washing and drying; S2: placing the dried paper in an inert atmosphere, performing heat treatment under sealed conditions, and applying a stress of 36 to 500 Pa to obtain the hard carbon material.
[0005] Patent CN116873902A prepares hard carbon with low defectivity and high crystallinity by pickling and applying stress, improving the first coulombic efficiency and specific capacity; however, the pickling process is relatively complicated and costly, and also involves issues such as waste liquid treatment. In addition, the patent only improves the first coulombic efficiency and specific capacity, and does not mention the deposition of sodium metal after long cycles of hard carbon at low working voltage, which will significantly affect the development of sodium ion batteries. Summary of the invention
[0006] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a fibrous self-supporting hard carbon negative electrode with both high first efficiency and ultra-high specific capacity. The use of a pre-oxidation strategy to oxidatively modify the precursor material is beneficial to protecting the structural stability of the material and improving the carbon yield; and in the subsequent high-temperature carbonization process, the graphite plate is used to induce the oxidation and reduction of oxygen-containing functional groups to generate small molecular gases and escape, which is beneficial to the regulation of the carbon layer inside the material, improve the degree of graphitization of the material, and thus improve the first efficiency of the material. Different from the complex process, high cost and environmental problems caused by solution treatment modification, the present invention prepares a fibrous self-supporting hard carbon negative electrode material with both high first efficiency and ultra-high specific capacity through a simple pre-oxidation strategy and high-temperature carbonization method. At the same time, this fibrous self-supporting structure is conducive to the reversible stripping / deposition of sodium metal at a low operating voltage.
[0007] A first aspect of the present invention provides a method for preparing a fibrous self-supporting hard carbon negative electrode, comprising the following steps:
[0008] Step 1, placing a fibrous self-supporting precursor between two graphite plates, and then placing it in a muffle furnace at 180-280° C. for pre-oxidation for 3-10 hours to obtain a pre-oxidized fibrous self-supporting precursor;
[0009] Step 2, placing the pre-oxidized fibrous self-supporting precursor between two graphite plates, and then placing it in a tube furnace, and carbonizing it at 1000-1500° C. in an inert atmosphere for 1-6 hours to obtain a fibrous self-supporting hard carbon negative electrode;
[0010] In step 1, the carbon chain structure of the precursor is oxidatively rearranged by pre-oxidation to introduce oxygen-containing functional groups; in step 2, the introduced oxygen-containing functional groups are oxidized and reduced using a graphite plate during high-temperature carbonization, and the carbon layer inside the material is regulated by the escape of gas molecules. The prepared fibrous self-supporting hard carbon negative electrode has a rich closed-pore structure and is formed by a large number of short-range ordered and long-range disordered carbon layers stacked together.
[0011] Furthermore, in step 1, the fibrous self-supporting precursor is a flexible material having a fibrous three-dimensional network cross-linked structure, and the thickness is 10 to 300 μm. More preferably, the flexible material having a fibrous three-dimensional network cross-linked structure is a low-cost commercial paper towel, and the thickness is 140 to 170 μm.
[0012] Furthermore, the fibrous self-supporting precursor is paper or a flexible material having a fibrous three-dimensional network cross-linked structure prepared by electrospinning, melt spinning, self-assembly, hydrothermal method, etc.
[0013] Furthermore, in step 1, the pre-oxidation heating rate is 0.5 to 3°C / min. More preferably, the pre-oxidation temperature is 220 to 250°C, the heating rate is 2 to 3°C / min, and the pre-oxidation time is 6 to 10 hours.
[0014] Further, in step 2, the high temperature carbonization heating rate is 0.5-3°C / min. More preferably, in step 2, the high temperature carbonization temperature is 1200-1400°C, the heating rate is 2-3°C / min, and the carbonization time is 2-5h.
[0015] Furthermore, the inert atmosphere in step 2 is argon or nitrogen.
[0016] Furthermore, the graphite plate is a graphite plate with a purity greater than 99.9% and a smooth surface.
[0017] The second aspect of the present invention is to provide a fibrous self-supporting hard carbon negative electrode prepared by the above-mentioned preparation method, which has a rich closed-pore structure and is formed by stacking a large number of short-range ordered and long-range disordered carbon layers. It is a self-supporting negative electrode material with a fibrous three-dimensional network cross-linked structure without the addition of a current collector, conductive agent and binder.
[0018] The third aspect of the present invention is to provide the use of the above-mentioned fibrous self-supporting hard carbon negative electrode as the negative electrode of a sodium ion battery. Using a sodium metal sheet as the counter electrode, 1 mol / L NaPF 6 The diethylene glycol dimethyl ether solution is used as the electrolyte and the glass fiber GF / A is used as the diaphragm.
[0019] The fourth aspect of the present invention provides the use of the above-mentioned fibrous self-supporting hard carbon negative electrode as a sodium storage, lithium storage, potassium storage, and zinc storage material.
[0020] Advantages and beneficial effects of the present invention:
[0021] 1. The present invention utilizes the fibrous three-dimensional network cross-linked structure of the self-supporting hard carbon negative electrode to effectively construct a conductive network, which can improve the conductivity of the negative electrode and reduce the use of conductive agents, binders and current collectors, thereby effectively improving the first-cycle coulomb efficiency and energy density of the battery.
[0022] 2. The present invention proposes for the first time to use the fibrous three-dimensional network cross-linked structure of the self-supporting hard carbon negative electrode to achieve reversible deposition and stripping of sodium metal deposited under low working voltage during the charging and discharging process, effectively compensating for the disadvantage of low specific capacity of the traditional sodium storage mechanism, and can also effectively avoid battery failure and safety problems caused by sodium metal deposition during the charging and discharging process. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 is a high resolution transmission electron microscopy (HRTEM) image of Examples 1-4;
[0024] Figure 2 The scanning electron microscope (SEM) images of Example 1, Comparative Example 1 and Comparative Example 2 are shown;
[0025] Figure 3 is the Raman spectrum (Raman) of Example 1-4;
[0026] Figure 4 is the X-ray diffraction (XRD) spectra of Examples 1-4;
[0027] Figure 5 The button cell prepared with the working electrode of Example 1 (without current collector, conductive agent and binder) was charged at a current density of 0.1C with a cut-off capacity of 500-1000 mAh g -1 The first cycle charge and discharge curve diagram for the discharge end condition;
[0028] Figure 6 The button cell prepared with the working electrode of Example 2 (without current collector, conductive agent and binder) was charged at a current density of 0.1C with a cut-off capacity of 500 mAh g -1 The first cycle charge and discharge curve diagram for the discharge end condition;
[0029] Figure 7 The button cell prepared with the working electrode of Example 3 (without current collector, conductive agent and binder) was charged at a current density of 0.1C with a cut-off capacity of 500 mAh g -1 The first cycle charge and discharge curve diagram for the discharge end condition;
[0030] Figure 8 The button cell prepared with the working electrode of Example 4 (without current collector, conductive agent and binder) was charged at a current density of 0.1C with a cut-off capacity of 500 mAh g -1 The first cycle charge and discharge curve diagram for the discharge end condition;
[0031] Fig. 9 The first cycle charge-discharge curve of a button cell prepared by using comparative example 1 as the working electrode (comparative example 1, conductive agent and binder are mixed with an appropriate amount of deionized water in a mass ratio of 8:1:1 and coated on aluminum foil) and discharged to 0.01V at a current density of 0.1C;
[0032] Fig.10 The first cycle charge-discharge curve of a button cell prepared by using comparative example 2 as the working electrode (comparative example 2, a conductive agent and a binder are mixed with an appropriate amount of deionized water in a mass ratio of 8:1:1 and coated on an aluminum foil) and discharged to 0.01V at a current density of 0.1C;
[0033] Fig.11The cycle performance comparison diagram of button batteries prepared in Example 1 (discharging to 0.01V at a current density of 0.1C and then discharging at a constant current for 300min) and Comparative Example 1 (discharging to 0.01V at a current density of 0.1C);
[0034] Fig.12 This is a comparison chart of the rate performance of button cells prepared in Example 1 (discharging to 0.01V at a current density of 0.1C and then discharging at a constant current for 300min) and Comparative Example 1 (discharging to 0.01V at a current density of 0.1C). DETAILED DESCRIPTION
[0035] The present invention is further described in detail below in conjunction with specific embodiments, and the following embodiments are only illustrative, not restrictive, and cannot be used to limit the scope of protection of the present invention. After reading the contents recorded in the present invention, various changes or modifications made to the present invention based on the principles of the present invention also fall within the scope defined by the claims of the present invention.
[0036] Example 1
[0037] This embodiment provides a method for preparing a fibrous self-supporting hard carbon negative electrode material, which specifically includes the following steps:
[0038] Step 1: Place a flexible low-cost commercial paper towel with a thickness of 140 to 170 μm and a fibrous three-dimensional network cross-linked structure between two graphite plates and pre-oxidize it in a muffle furnace. The pre-oxidation temperature is 240°C, the pre-oxidation time is 8 hours, and the heating rate is 3°C / min; after natural cooling, a pre-oxidized fibrous self-supporting precursor is obtained.
[0039] Step 2, placing the pre-oxidized fibrous self-supporting precursor obtained in step 1 between two graphite plates in a tubular furnace, under argon protection, with a carbonization temperature of 1300°C, a carbonization time of 3h, and a heating rate of 3°C / min.
[0040] The TEM image of the fibrous self-supporting hard carbon material prepared in this example is shown in FIG. Figure 1 As shown, it displays a rich closed-pore structure and is formed by the stacking of a large number of short-range ordered and long-range disordered carbon layers.
[0041] Example 2
[0042] This embodiment provides a method for preparing a fibrous self-supporting hard carbon negative electrode material. The difference from Embodiment 1 is that the carbonization temperature of the fibrous self-supporting hard carbon material in Step 2 is adjusted to 1200°C.
[0043] The TEM image of the fibrous self-supporting hard carbon material prepared in this example is shown in FIG. Figure 1As shown, similar to Example 1, it also shows an obvious closed-pore structure with a large number of short-range ordered and long-range disordered carbon layer structures.
[0044] Example 3
[0045] This embodiment provides a method for preparing a fibrous self-supporting hard carbon negative electrode material. The difference from Embodiment 1 is that the carbonization temperature of the fibrous self-supporting hard carbon material in Step 2 is adjusted to 1100°C.
[0046] The TEM image of the fibrous self-supporting hard carbon material prepared in this example is shown in FIG. Figure 1 As shown, it has an obvious closed-pore structure. Compared with Example 1, the number of closed pores and the number of long carbon layers are reduced.
[0047] Example 4
[0048] This embodiment provides a method for preparing a fibrous self-supporting hard carbon negative electrode material. The difference from Embodiment 1 is that in Step 1, the fibrous self-supporting precursor does not undergo a muffle furnace pre-oxidation process.
[0049] The TEM image of the fibrous self-supporting hard carbon material prepared in this example is shown in FIG. Figure 1 As shown, since this embodiment does not use pre-oxidation to oxidatively rearrange the precursor carbon chain structure, it exhibits a longer and thicker carbon layer structure.
[0050] Comparative Example 1
[0051] This comparative example provides a powdered commercial hard carbon (Kuraray) negative electrode plate, and the preparation of the plate specifically includes the following steps:
[0052] Step 1, mechanically mixing powdered commercial hard carbon (Kuraray) with a conductive agent and a binder in a mass ratio of 8:1:1 to obtain a negative electrode mixture;
[0053] Step 2, the negative electrode mixture in step 1 is mixed with deionized water in a solid-liquid ratio of 1:4 (wt%:wt%) to form a slurry, and the slurry is scraped on the surface of the aluminum foil using aluminum foil as a current collector, and vacuum dried at 80° C. for 12 hours;
[0054] Step 3: Cut the aluminum foil loaded with the negative electrode mixture in step 2 into discs with a diameter of 10 mm to obtain the negative electrode sheet of the battery. The active material loading is ~1.8 mg / cm 2 .
[0055] Comparative Example 2
[0056] This comparative example provides a fiber granular hard carbon negative electrode sheet. The difference from comparative example 1 is that the hard carbon raw material is changed, and specifically includes the following steps:
[0057] Step 1, crushing the fibrous self-supporting hard carbon material prepared in Example 1 by using a powder grinder to obtain a fibrous granular hard carbon material;
[0058] Step 2, mechanically mixing the fibrous granular hard carbon material in step 1 with a conductive agent and a binder in a mass ratio of 8:1:1 to obtain a negative electrode mixture;
[0059] Step 3, the negative electrode mixture in step 2 is mixed with deionized water in a solid-liquid ratio of 1:4 (wt%:wt%) to form a slurry, and the slurry is scraped on the surface of the aluminum foil using aluminum foil as a current collector, and vacuum dried at 80° C. for 12 hours;
[0060] Step 4: Cut the aluminum foil loaded with the negative electrode mixture in step 3 into discs with a diameter of 10 mm to obtain the negative electrode sheet of the battery. The active material loading is ~1.8 mg / cm 2 ;
[0061] The test results of the fibrous self-supporting hard carbon negative electrode materials prepared in the above-mentioned embodiments of the present invention and the negative electrode materials in the comparative examples were compared.
[0062] Experiment 1: High-resolution transmission electron microscopy test
[0063] The hard carbon materials prepared in Examples 1-4 were tested by high resolution transmission electron microscopy (HRTEM). Figure 1 As shown, the fibrous self-supporting hard carbon negative electrode material prepared in the embodiment has a typical hard carbon carbon layer structure, showing a rich closed-pore structure, and is formed by stacking a large number of short-range ordered and long-range disordered carbon layers.
[0064] Experiment 2: Scanning Electron Microscope Test
[0065] The hard carbon negative electrode sheets prepared in Example 1, Comparative Example 1 and Comparative Example 2 were tested by scanning electron microscope (SEM). Figure 2 As shown, the fibrous self-supporting hard carbon negative electrode prepared in the embodiment has a three-dimensional network cross-linked structure; the hard carbon negative electrodes of comparative examples 1 and 2 are typical granular types, and their particle sizes are all about 5 μm.
[0066] Experiment 3: Raman spectroscopy test
[0067] The fibrous self-supporting hard carbon negative electrode materials prepared in Examples 1-4 were tested by Raman spectroscopy. The results are as follows: Figure 3 As shown, the Raman spectrum shows two independent characteristic peaks, D and G, located at 1340 cm -1 and ~1580cm -1 , confirming that it has an amorphous carbon structure. By Raman spectroscopy, the peak shift of 1340 cm -1 The peak area near ID With displacement 1580cm -1 The peak area near I G The ratio of the higher I D / I G Values indicate more amorphous carbon structure.
[0068] Experiment 4: X-ray diffraction test
[0069] The fibrous self-supporting hard carbon negative electrode materials prepared in Examples 1-4 were subjected to X-ray diffraction (XRD) testing. The test results are as follows: Figure 4 As shown, the prepared example exhibits two broad characteristic peaks at around 23.0° and 44.0°, corresponding to the (002) and (100) diffraction crystal planes, respectively, which are typical properties of amorphous carbon.
[0070] Experiment 5: Battery assembly and testing:
[0071] The fibrous self-supporting hard carbon material in each example was used as the working electrode (without current collector, conductive agent and binder), and the sodium metal sheet was used as the counter electrode. 1 mol / L NaPF 6 The diethylene glycol dimethyl ether solution was used as the electrolyte, and the glass fiber GF / A was used as the diaphragm; the powdered hard carbon in Comparative Example 1-2 was mixed with conductive carbon black (Super P) and sodium carboxymethyl cellulose binder (CMC) at a mass ratio of 8:1:1, homogenized with deionized water as a dispersant and evenly coated on aluminum foil, and then vacuum dried at 80°C and cut into 10 mm diameter discs (loading of ~1.8 mg / cm 2 ) ; CR2032 button cells were assembled in a glove box with argon as the protective atmosphere.
[0072] Charge and discharge test:
[0073] The charge and discharge test procedure of the button cell assembled with the fiber-shaped self-supporting hard carbon negative electrode as the working electrode is to let it stand for 12 hours, then discharge it to 0.01V at a current density of 0.1C, and then discharge it at a constant current for 300 minutes (or set the cut-off capacity to 500-1000mAhg -1 The discharge end condition is then recharged to 2.0 V. At the same time, the first cycle discharge capacity of the button cell using the fiber-shaped self-supporting hard carbon negative electrode as the working electrode can be as high as 500-1000 mAh g -1 .
[0074] The charge and discharge test procedure of the button cell assembled with the pole piece prepared by coating the powdered hard carbon material is the traditional hard carbon negative electrode test method, which is to stand for 12 hours, then discharge to 0.01V at a current density of 0.1C, and then charge to 2.0V;
[0075] Testing powdered hard carbon negative electrode materials using the above-mentioned fibrous self-supporting hard carbon negative electrode testing method will cause battery short circuit and failure.
[0076] The electrochemical performance tests were all carried out at room temperature.
[0077] Figure 5-10 The first cycle charge and discharge curves of the button type batteries of Examples 1 to 4 and Comparative Examples 1 to 2 are shown in Table 1. The performance comparison of the button type batteries of the embodiments and comparative examples is shown in Table 1.
[0078] Table 1 Comparison of button cell performance
[0079]
[0080] By comparing the charge and discharge curves of Example 1-4 and Comparative Example 1-2, when the first cycle discharge to 0.01V, the specific capacity of Comparative Example 1-2 is only 331.05 and 361.00 mAh g -1 , continued discharge will trigger the growth of sodium dendrites and cause battery short circuit and failure; Examples 1-4 can continue to discharge after discharging to 0.01V. At this time, the embodiments utilize the fibrous three-dimensional network cross-linked structure of the self-supporting hard carbon negative electrode to perform reversible deposition and stripping of sodium metal at a low operating voltage (<0.01V), thereby achieving the goals of ultra-high specific capacity and high initial efficiency.
[0081] The fibrous three-dimensional network cross-linked structure of the self-supporting hard carbon negative electrode proposed in the present invention can effectively realize the reversible deposition and stripping of the sodium metal deposited under low working voltage during the charge and discharge process, thereby compensating for the disadvantage of low specific capacity of the traditional sodium storage mechanism and achieving the goal of high specific capacity hard carbon; at the same time, the fibrous three-dimensional network cross-linked structure of the self-supporting hard carbon negative electrode reduces the use of conductive agents, binders and current collectors, and effectively improves the first-cycle coulombic efficiency of the battery.
[0082] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing a fibrous self-supporting hard carbon negative electrode, characterized in that: The following steps are involved: Step 1, placing a fibrous self-supporting precursor between two graphite plates, and then placing it in a muffle furnace at 180-280° C. for pre-oxidation for 3-10 hours to obtain a pre-oxidized fibrous self-supporting precursor; Step 2, placing the pre-oxidized fibrous self-supporting precursor between two graphite plates, and then placing it in a tube furnace, and carbonizing it at 1000-1500° C. in an inert atmosphere for 1-6 hours to obtain a fibrous self-supporting hard carbon negative electrode; In step 1, the carbon chain structure of the precursor is oxidatively rearranged by pre-oxidation to introduce oxygen-containing functional groups; in step 2, the introduced oxygen-containing functional groups are oxidized and reduced using a graphite plate during high-temperature carbonization, and the carbon layer inside the material is regulated by the escape of gas molecules. The prepared fibrous self-supporting hard carbon negative electrode has a rich closed-pore structure and is formed by a large number of short-range ordered and long-range disordered carbon layers stacked together.
2. The method for preparing a hard carbon negative electrode according to claim 1, characterized in that: In step 1, the fibrous self-supporting precursor is a flexible material having a fibrous three-dimensional network cross-linked structure and has a thickness of 10 to 300 μm.
3. The method for preparing a hard carbon negative electrode according to claim 2, characterized in that: The fibrous self-supporting precursor is paper or a flexible material having a fibrous three-dimensional network cross-linked structure prepared by electrospinning, melt spinning, self-assembly or hydrothermal method.
4. The method for preparing a hard carbon negative electrode according to claim 1, characterized in that: In step 1, the pre-oxidation heating rate is 0.5-3°C / min.
5. The method for preparing a hard carbon negative electrode according to claim 1, characterized in that: In step 2, the high temperature carbonization heating rate is 0.5-3°C / min.
6. The method for preparing a hard carbon negative electrode according to claim 1, characterized in that: The graphite plate is a graphite plate with a purity greater than 99.9% and a smooth surface.
7. A fibrous self-supporting hard carbon negative electrode prepared according to the preparation method according to any one of claims 1 to 6.
8. Use of the fibrous self-supporting hard carbon negative electrode according to claim 7 as a negative electrode for a sodium ion battery.
9. The use according to claim 8, characterized in that: Sodium metal sheet was used as the counter electrode, 1 mol / L NaPF6 solution in diethylene glycol dimethyl ether was used as the electrolyte, and glass fiber GF / A was used as the diaphragm.
10. Use of the fibrous self-supporting hard carbon negative electrode according to claim 7 as a sodium storage, lithium storage, potassium storage, or zinc storage material.
Citation Information
Patent Citations
Silicon composite nanofiber, silicon composite nanofiber membrane and preparation method and application of silicon composite nanofiber membrane
CN115966658A
Graphene coated hard carbon fiber composite material and preparation method thereof
CN116864657A
Self-supporting biomass carbon negative electrode material and preparation method thereof
CN118419906A